CFD analysis of a SD 7003 airfoil with a local correlation based transition and turbulence model - Islam, Mazharul; Langfeldt, Felix; Fürst, Jiri; Wood, David H. (2016)
The SD 7003 is one of the airfoils which have been investigated quite elaborately in the pastat dierent Reynolds numbers. In this article, a widely used open-source Computational FluidDynamics (CFD) toolbox has been used mainly to investigate the (i) aerodynamics coecientsand (ii) boundary layer transitional behaviors of SD 7003 airfoil using a local correlation based gamma-Re_theta [1] transition and turbulence model. Several researchers have proposed dierentcorrelations in the past which can be used in the gamma-Re_theta model and in this article, five correlations have been used to analyze SD 7003. The results obtained from the research work have been compared with earlier experimental and computational results for validation.